IJTIHAD POLITIK KYAI: PERGESERAN OTORITAS KHR. ACH. FAWAID AS’AD SITUBONDO - Nawawi Nawawi; Wawan Juandi (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2021)
This study found that the relationship between santri and kyai is a pattern of emotional relations such as the feudal system. Kyai has three pillars. They are the mass base as a pattern of social structure, the ulama base as a leadership structure and the cultural base as a scientific basis. However, these three pillars have experienced a shift due to the kyai's entry into practical politics due to his political ijtihad. This shift places the authority of the kyai from a spiritual teacher (central position) to a politician (peripheral position). In this case, the kyai is still obeyed when he is in a central position as a spiritual teacher and not obeyed when his position is marginal as a politician. Of course, this becomes an authority dilemma as experienced by kyai Fawaid who is directly involved in practical politics. The involvement of kyai Fawaid in politics does not belong to the opportunist category but is a form of concern for carrying out the commands of ma'ruf nahi munkar in social transformation. Kyai Fawaid's political ijtihad was strongly influenced by the habituation of Islamic boarding schools based on fiqh. Habituation here is to create a political situation and condition (persistence life situation) through a process of internalization and habituation in accordance with the values ​​of the pesantren, not to be carried away by the flow of political habituation which is always pragmatic and materialistic. The result of his Ijitihad that winning in politics by deception must be abandoned and losing in the right way must be maintained. Thus, the findings of this study can invalidate the theory from the results of research that has been carried out by Ernst Utrecht, Mochtar Naim, Daneli Lev, Justus van der Kroef, Arnold Brackman and Munir Mulkan, where they say that kyai or pesantren of Nahdlatul Ulama who participate politics are opportunists.